Strategic obfuscation and consumer protection policy in financial markets: Theory and experimental evidence - Yiquan Gu; Tobias Wenzel (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2012)
This paper studies obfuscation decisions by firms in retail financial markets theoretically and experimentally. We show that more prominent firms are more likely to obfuscate. While prominent firms always choose maximum obfuscation, the obfuscation by less prominent firms depends on the degree of asymmetry in prominence and consumer protection policy. We evaluate the impact of a consumer protection policy that limits the scope of obfuscation. We show that such a policy may not be effective as less prominent firms may increase their obfuscation practice.
Keywords: G20; D14; D18; C92; 330; Obfuscation; Financial markets; Consumer protection; Experiment